Military discourse. Characteristics and types - Liana ROBU (MACOVEI) (Diversitate si Identitate Culturala in Europa)
Efficient communication is essential in any field, being vital in dynamic, high-stakes environments such as the military, where clear and accurate communication safeguards troop safety and mission success. In this paper, we delve into the peculiarities of military communication, aiming to point out some of the features of its different types. The focal point in our endeavor – the ceremonial speeches in the Romanian Navy – are going to be analyzed taking into consideration the rules and regulations that govern military communication in the Romanian Armed Forces, on the one hand, and the rhetorical and public relations strategies used, on the other hand. How the military communicate, and the types of discourse and strategies they use vary according to context. For instance, internal communication is defined by precise, concise and direct language needed to coordinate missions, to give orders and to report back from the field. Ceremonies are prone to the same military rigor, the purpose of communication being different, however. In this case, speeches become a means to bring forward the discipline within the military institution and to promote its core values: respect, unity and honor.